The Relationship Of Employment Status And Educational Status Of Prospective Brides On The Incident Of Early Marriage In The Kua Region Of Jombang District (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstract Early marriage is an movement to tie two individuals of the inverse sex who are still young people into one family bond. Cases of early marriage in Jombang Rule are still tall. January-November 2022 alone, there were 920 individuals. Pudji Umbaran, Head of DPPKB-PPPA Jombang, said the information is up to November. The overall number of women's to begin with relational unions until November 2022 is 9,270 individuals. This inquire about strategy employments an expository study with a Case Control investigate plan and a Review approach. The information investigation utilized is univariate investigation utilizing recurrence dissemination and bivariate investigation. The information were analyzed factually utilizing the Chi-square test employing a certainty level of 95% with an α of 5% so that in factual calculations the P esteem <0.05 shows that there's a relationship between the autonomous variable and the subordinate variable. The results of the examination of business status have a p-value of 0.000, showing that there's a relationship between employment status and the event of early marriage. In the mean time, work status features a p-value of 0.000, there's a relationship between instructive status and the event of early marriage. From the comes about of this inquire about it can be concluded that there's a relationship between instructive status and business status and the frequency of early marriage.